RESPONSE OF OIL PALM SEEDLINGS (Elaeis Guineensis Jacq) IN PRE-NURSERY TO THE APPLICATION OF SEVERAL TYPES OF MANURE - ii, YULIATRI; Patri Enati, Nin; Agustia, Ratna; Sulastri; DS, Fefriyanti D.S; Erlinda, Rita (Atech-i, 2025)
This study aimed to evaluate the effect of various types of organic manure on the growth of oil palm (Elaeis guineensis Jacq.) seedlings during the pre-nursery stage. The experiment was conducted at the Experimental Garden of Politeknik Pertanian Negeri Payakumbuh using a Completely Randomized Design (CRD) with four treatments: without manure (P0), rabbit manure 200 g/polybag (P1), duck manure 200 g/polybag (P2), and chicken manure 200 g/polybag (P3), each replicated four times. Observed parameters included plant height, stem diameter, and number of leaves. The results showed that chicken manure (P3) produced the highest seedling height (21.75 cm) and the largest stem diameter (0.94 cm), significantly higher than the control. Rabbit manure (P1) and duck manure (P2) also improved growth compared to the control, although not significantly different from P3 in plant height. The number of leaves did not significantly differ among treatments, yet all seedlings met the criteria for transfer to the main nursery (≥4 leaves). The superiority of chicken manure is presumably due to its low C/N ratio, which accelerates nutrient mineralization, particularly nitrogen. These findings recommend chicken manure as an effective option to enhance oil palm seedling growth at the pre-nursery stage. Keywords: oil palm, pre-nursery, organic manure, C/N ratio